Records Committee review for rare bird sighting of Lesser Black-backed Gull at Lock and Dam 19 in Keokuk, 1986 - Cecil, Robert I.et al (1986)
Records Committee for a Lesser Black-backed Gull at Lock and Dam 19 in Keokuk in Lee County, IA on October 20, 1986. Includes a record review document with votes, an article in Iowa Bird Life, summary of the review, and two documentation forms submitted to the committee. Epson - sheet feed